Comparison of intravenous lignocaine and esmolol in attenuating hemodynamic response and cough reflex during extubation in hypertensive patients under general anaesthesia - Ng, CY; Liu, CY; Cheah, SK; Ooi, Joanna Su Min; Rufinah Teo (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Tracheal extubation carries higher complication rates compared to intubation during general anaesthesia (GA). Thus, various drugs are used to attenuate hemodynamic responses and cough reflex during extubation. We investigated if intravenous (IV) lignocaine and esmolol, given prior extubation, was able to achieve that in hypertensive patients under GA. In this prospective, double-blinded, randomised controlled study, 68 hypertensive patients on treatment undergoing GA were analysed. Group L received IV lignocaine 1 mg/kg while Group E received IV esmolol 1.5 mg/kg, 2 minutes before extubation. Heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP) and mean arterial pressure (MAP) were recorded at the following interval: before study drug administration (T-0), prior extubation (T-1), 1 minute (T-2), 3 minutes (T-3), 5 minutes (T-4) and 10 minutes (T-5) post-extubation. Group L showed significantly increase in HR at T-2 while SBP and MAP increased significantly from T-1 until T-5. Group E showed a significant reduction in HR at T-1 up to T-5 and significantly lower HR at T-1 and T-2 compared to Group L. Group E showed stable SBP, DBP and MAP at all intervals. In conclusion, IV esmolol at 1.5 mg/kg was able to attenuate the hemodynamic response more pronounced when compared to IV lignocaine at 1 mg/kg from extubation stress in patients with hypertension on treatment. Both lignocaine and esmolol were equally effective in suppressing cough reflex during extubation.